Exploring Adolescent Moderate-to-Vigorous Physical Activity in China: Mediating Roles of School Climate, Perceived Barriers, and Physical Education Satisfaction - Li Q; Li L; He X; Wang H (Risk Management and Healthcare Policy)
Qianyuan Li,1 Li Li,1 Xianyi He,2 Huilin Wang3 1School of Physical Education, Hunan University of Science and Technology, Xiangtan, 411201, People’s Republic of China; 2College of Physical Education, Hunan Normal University, Changsha, 410017, People’s Republic of China; 3School of Business, Hunan University of Science and Technology, Xiangtan, 411201, People’s Republic of ChinaCorrespondence: Huilin Wang, School of Business, Hunan University of Science and Technology, Xiangtan, 411201, People’s Republic of China, Email 1150141@hnust.edu.cnBackground: The lack of physical activity poses a major challenge to adolescents’ healthy physical and mental development. Despite growing attention, research on how the school physical activity climate affects Chinese adolescents’ participation in moderate-to-vigorous physical activity (MVPA) remains scarce. This study explores this relationship through the lens of ecological systems theory, focusing on the mediating roles of physical education satisfaction and perceived barriers. It also proposes strategies to promote MVPA among Chinese adolescents.Methods: This cross-sectional study employed convenience and snowball sampling methods to examine the impact of the school physical activity climate on adolescent participation in MVPA. It also explored the mediating roles of physical education satisfaction and perceived barriers. Four variables in the study were measured using established scales: Physical Activity Climate, Perceived Barriers to Physical Activity, Physical Education Satisfaction, and Physical Activity Assessment. The data were analyzed using AMOS v.23 to construct and test a structural equation model.Results: A total of 612 adolescents aged 12 to 18 from six key middle schools in central China participated in the study. The findings showed that a positive school physical activity climate significantly promotes MVPA participation. Physical education satisfaction positively correlated with MVPA (β = 0.322, p < 0.001), while perceived barriers negatively correlated with both physical education satisfaction (β = − 0.449, p < 0.001) and MVPA (β = − 0.366, p < 0.001). Satisfaction with physical education and perceived barriers mediated the relationship between the school climate and MVPA, emphasizing their importance in shaping adolescent physical activity behavior. Confirmatory factor analysis (CFA) results (χ²/df = 1.928, GFI = 0.969, AGFI = 0.956, NFI = 0.962, CFI = 0.981, RMSEA = 0.037) confirmed the model’s robustness and good fit.Conclusion: Adolescents in a positive physical activity climate are more likely to overlook perceived barriers, enjoy higher satisfaction in PE classes, and actively engage in MVPA. Schools and educators are advised to foster a supportive physical activity environment to boost adolescent MVPA participation, considering the unique context of China’s educational system.Keywords: adolescents, physical activity climate, perceived barriers, physical education satisfaction, moderate-to-vigorous physical activity